Evaluating the Success of Circular Economy Models in Reducing Waste: Evidence from Europe and China - Obani, Izuchukwu Precious; Obani, Zino Izu; Anaeto, Prof Frank Chudi; Akroh, Theresa Ojevwe; Nwachukwu, Chinwe Sheila (American Journal of Biology and Natural Sciences, 2025)
The circular economy (CE) model has emerged as a transformative strategy for reducing waste, promoting resource efficiency, and mitigating environmental degradation. Unlike the traditional linear economy, which follows a “take-make-dispose” approach, the circular economy emphasizes waste prevention, material reuse, recycling, and sustainable production. This study evaluates the success of circular economy models in Europe and China, two global leaders in adopting and implementing CE frameworks, to assess their effectiveness in waste reduction and resource management. Europe has taken a policy-driven approach, with comprehensive regulations such as the EU Circular Economy Action Plan and the Waste Framework Directive, which have led to significant improvements in recycling rates, landfill reduction, and eco-innovation in product design. The EU’s Extended Producer Responsibility (EPR) schemes and strict waste management regulations have also played a crucial role in reducing industrial and municipal waste, while fostering the development of sustainable business models. On the other hand, China’s circular economy strategy is heavily influenced by industrial symbiosis and large-scale waste-to-resource initiatives, driven by policies such as the Circular Economy Promotion Law and Made in China 2025. China has focused on scaling up circular industrial parks, urban mining, and electronic waste (e-waste) recycling, demonstrating a unique approach that integrates economic development with environmental sustainability. Despite these successes, both Europe and China face persistent challenges in fully realizing circular economy goals. Policy enforcement gaps, economic barriers, and industry adaptation hurdles continue to pose obstacles, while issues related to consumer participation, supply chain integration, and technological advancements remain critical factors influencing long-term success. Additionally, the effectiveness of CE policies varies between different sectors and regions, highlighting the need for localized strategies and adaptive frameworks. This study underscores the necessity of multistakeholder collaboration, involving governments, businesses, and consumers, to enhance circular economy performance. It also highlights key lessons for other nations aiming to transition toward a zero-waste, resource-efficient future. By integrating circular economy principles into global sustainability efforts, CE models can play a pivotal role in reducing environmental impact, conserving natural resources, and fostering long-term economic resilience. Strengthening global partnerships, investing in innovative technologies, and enhancing regulatory frameworks will be essential for maximizing the potential of circular economy models in achieving a truly sustainable and waste-free world.